A Novel Nitrocellulose Filter Membrane Based Partitioning-Reverse Transcription Using Repora-6 RNA Aptamer In Detecting Erythropoietin (EPO) - Ravinderan, Presela (2015)
Recombinant human EPO (rHuEPO), a mimetic of endogenous EPO is widely misused by athletes as a performance enhancer, a phenomenon known as doping. Current methods of detecting rHuEPO doping are via isoelectric-focusing (IEF)-doubleimmunoblotting, Sarcosyl-PAGE (SAR PAGE) and lateral flow test, which are antibody-based approach using anti-EPO antibody. The caveats associated with anti- EPO antibodies have spurred the interest to adopt an alternative molecular recognition element (MRE) in detecting EPO.